2012
DOI: 10.1016/j.jvs.2011.07.072
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1 promotes endothelial cell angiogenic behavior in vitro and improves muscle perfusion in vivo in response to ischemic injury

Abstract: Objectives The angiogenic drive in skeletal muscle ischemia remains poorly understood. Innate inflammatory pathways are activated during tissue injury and repair, suggesting that this highly conserved pathway may be involved in ischemia-induced angiogenesis. We hypothesize that one of the endogenous ligands for innate immune signaling, high mobility group box 1 (HMGB1), in combination with autophagic responses to hypoxia or nutrient deprivation plays an important role in angiogenesis. Methods Human dermal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 38 publications
3
75
0
Order By: Relevance
“…Hypoxia Induces HMGB1 Release from HPAECs-Several groups have previously shown that exposure to acute hypoxia leads to the release of HMGB1 from a variety of cell types, including systemic endothelial cells (6,21). It has, however, not been explored in pulmonary endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxia Induces HMGB1 Release from HPAECs-Several groups have previously shown that exposure to acute hypoxia leads to the release of HMGB1 from a variety of cell types, including systemic endothelial cells (6,21). It has, however, not been explored in pulmonary endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, HMGB1 has been shown to stimulate cell migration and angiogenesis in HUVECs (6,(22)(23)(24). We were, therefore, curious to know whether we could recapitulate these results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[69][70][71][72] In addition, HMGB1 is reported to possess proangiogenic activity. [73][74][75][76] Its ability to promote proliferation, migration, and differentiation of several cell types, particularly those involved in angiogenesis, prompted us to examine the ability of HMGB1 to mobilize EPCs from the bone marrow. We observed significant mobilization of bone marrow EPCs and their initial sequestration in the spleen.…”
Section: Systemic Inflammation: Three Waves Of Danger Signalingmentioning
confidence: 99%
“…Whereas most have focused on the identification and testing of proangiogenic compounds or cellular therapies, there has been much less emphasis on evaluating the role of modulating inflammation to improve tissue recovery from the ischemic insult. We and others have investigated the role of toll-like receptor (TLR) activation in promoting angiogenesis and muscle recovery in a murine model of hindlimb ischemia (7)(8)(9)(10)(11)(12)(13)(14). TLRs mediate innate immune responses to bacterial components, including gram-negative bacterial lipopolysaccharide (LPS) (TLR4) and gram-positive bacterial lipoproteins (TLR2) (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%